SPECIAL METHODS OF SCHOOL HEALTH PROGRAMME FOR SPECIAL NEEDS CHILDREN IN DENTISTRY - Pranoto, Amelia Elizabeth; Wahjuningsih, Endah; Paramita, Ayulistya; Tsurayya, Nur; Wardhani, Istien; Apsari, Anindita; Puspita, Sinta; Teguh, Paulus Budi; Juniar, Eriza; Ayu, Dyah; Sarianoferni, Sarianoferni; Prameswari, Noengki; Rahardjo, Pambudi; Rizal, Mohammad Basroni; Hermanto, Eddy (LPPM Institut Pendidikan Nusantara Global, 2023)
School health program is a program of preventive promotional activities in the field of dentistry using the method “trainer of trainer” or abbreviated as ToT. The program is organized by the Indonesian Association of Dentists (PDGI) together with dental faculties across Indonesia as trainers and multinational company as facilitator. The goal of this program is to create a generation of a nation that will be free of tooth cavities by 2030. Teachers and parents of students with special needs are the target audience for this training, enabling them to carry out morning and night toothbrushing activities for good dental and oral health. ToT's activities include two things: giving advice to teachers and students' parents and brushing their teeth in the morning and evening for 21 days. The problem is that children with special needs do not have the same abilities as other children in terms of receiving information, responding to teaching, and applying what has been taught. Low levels of independence and varying levels of learning difficulties are challenges for trainees. Special methods in teaching morning and night toothbrush activities should be applied well to both teachers and parents of students with special needs, such as how to brush their teeth, the habits of brushing the teeth properly, the use of special brushes, and tips and tricks that can be implemented by the teacher and parents so that children with special requirements can run the program.